Zespołowa organizacja pracy (teamwork) w niemieckich bibliotekach uniwersyteckich - Zdzisław Gębołyś (Biblioteka)
The article discusses the method of team organization of work (teamwork) employed in German university and academic libraries. The starting point for the discussion is the description of the shortcomings of the ubiquitous functional organizational model used in academic libraries. This model features numerous flaws, particularly noticeable in the decision making process carried out at the hierarchical level. The solution enabling elimination or, at least limiting the adverse shortcomings hampering the development of any library, can be the concept of work organization o f teamwork. This method aligns employee mindsets towards a specific business purpose (goals and tasks to be fulfilled) and employs abilities and skills of individual members of teams to a higher degree than before. The teamwork concept, originated in big industry, has now ceased to be just a theory in libraries. It has been used successfully in German university, academic and public libraries. With the example of three university libraries - the Konstanz University Library, Munich University of Technology Library and Dortmund University Library, the author presents the main features of the new organizational model and the stages of its implementation in the said libraries. In a word, teamwork means a change in the organizational structure of a library, cuts in the middle managerial staff, introduces a completely different management system and, additionally, a change in the mentality of the staff. Rewording the above, all this can simply correspond to a great change in the organizational culture of the library.